Catalyzed Michael addition, polycondensation, and the related performance of Diels–Alder self‐healing crosslinked polyamides. Issue 4 (7th February 2022) - Chen, Shuo; Feng, Yu; Zhang, Zhi‐Yuan; Li, Xiang‐Yuan; Zhang, Jun‐Ying; Zhao, Jing‐Bo
Abstract: Diels–Alder (DA) addition is an efficient method to repair damages at mild conditions. It is often used in self‐healing polyurethanes and epoxy resins and seldom used in cross‐linked polyamides (cPAs). Michael addition becomes a useful method to synthesize cPAs. However, no efficient way has been established to conduct double‐addition of primary amines. In this work, organic catalyzed Michael addition and polycondensation were established to prepare polyamide oligomers with furan pendent groups (pFU‐PAs), and a DA addition was adopted to prepare self‐healing cross‐linked polyamides (SH‐cPAs). A bulk double Michael addition of furfurylamine and methyl acrylate was performed at 30–70°C in the presence of 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD), 7‐methyl‐1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (MTBD), or 4‐(N, N‐dimethylamino) pyridine (DMAP), and a high yield of furfurylamine‐N, N‐bis(methyl propionate) (FA‐BMP) was prepared. The catalytic activity order is MTBD>TBD >>DMAP in Michael addition. Melt polycondensation of FA‐BMP with bis(2‐aminopropyl) polypropyleneglycol and hexamethylene diamine was catalyzed by MTBD and N, N′‐diphenylthiourea. The DA addition of 1, 5‐bismaleimido‐2‐methylpentane and pFU‐PAs was monitored by FT‐IR, 1 H NMR, DSC, polarizing optical microscopy, and gel content. In these catalyzed processes, the structures of FA‐BMP, pFU‐PAs, and SH‐cPAs were controlled easily, and the SH‐cPAs showed good mechanical property and excellent self‐healing performance of 88%–98%. Abstract :